A multinational telemedicine systems for disaster response opportunities and challenges - Doarn, Charles; Latifi, Rifat; Hostiuc, Filip; Arafat, Raed; Zoicas, Claudiu (NATO science for peace and security series.nE,pHuman and societal dynamics ;vvol. 130, 2017)
In the aftermath of a disaster, medical infrastructure is often significantly impacted or destroyed in the affected zone. Recognizing the need for an effective system for deployment in disaster zones, the Emerging Security Challenges Division within NATO's Science for Peace and Security Program (SPS) initiated the development of a multinational telemedicine system (MnTS). Such a system can improve access to health services and increase survival rates in emergency situations spanning both geographical and time zones. This book presents a review of this NATO-funded MnTS, and follows the thematic approach to its development. The book is divided into 14 chapters; Chapter 1 includes a historical review of telemedicine and disasters and Chapter 2 provides a historical perspective of NATO's efforts in the field of telemedicine, while Chapters 3 - 12 summarize the development of the MnTS. Critical components of the MnTS are addressed, such as overall organizational structure, the integration of information technology, legal and regulatory considerations, and outreach and public awareness. The evaluation of the MnTS in a field exercise is described, and the book closes with a final summary of the MnTS. The book addresses the challenges faced in deploying telemedicine following a disaster, such as IT, language, culture and legal issues, and provides a template for making telemedicine part of international disaster response